Managing the Sovereign-Bank Nexus - Dell'Ariccia, Giovanni; Ferreira, Caio.; Jenkinson, Nigel; Laeven, Luc. (Washington, D.C. : International Monetary Fund, 2018)
This paper reviews empirical and theoretical work on the links between banks and their governments (the bank-sovereign nexus). How significant is this nexus? What do we know about it? To what extent is it a source of concern? What is the role of policy intervention? The paper concludes with a review of recent policy proposals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet